Hemorrhagic syndrome as a consequence of the interaction of wafrarin and metronidazole - Eraković, Ivana; Baralić, Ivana (Archives of Pharmacy, 2022)
Warfarin is one of the most commonly used oral anticoagulants. It has narrow therapeutic range, wide interindividual variability and a significant number of interactions with drugs and food, and requires careful monitoring. Bleeding, as a consequence of warfarin overdose, is a common reason for hospitalization, but interactions of warfarin and other drugs are often overlooked. Patient J.K. on stable warfarin therapy, had perianal abscess surgery and was prescribed ciprofloxacin and metronidazole. After the operation, she also took diclofenac. A few days later, she was admitted to the hospital, due to GIT bleeding. In laboratory analyzes, normocytic anemia was registered, with a significant increase in INR-13.7. The analysis of the therapy revealed several potentially dangerous interactions. Numerous studies reported that metronidazole inhibits the CYP2C9 isoenzyme, predominantly responsible for warfarin metabolism. Most studies, that have evaluated the effect of NSAIDs on the warfarin, have shown a little or no effect. A few case reports and small studies, however, have noted increases in prothrombin time and bleeding episodes. Ciprofloxacin may not influence warfarin, anticoagulant effect in most patients, but more frequent INR measurements are recommended. The available evidence supports the hypothesis that metronidazole is a major factor for increased INR in the presented patient. If concomitant use cannot be avoided, dose reduction of warfarin should be considered, with more frequent monitoring of INR and symptoms/signs of bleeding. In addition, diclofenac, may not have significantly affected INR, but an increased risk of bleeding with its use cannot be ruled out.